Weight-adjusted waist circumference index and chronic diseases as predictors of depression risk in U.S. adults: a cross-sectional study with mediation analysis - Guo, Yali; Song, Meilin; Wang, Cuixiao (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to examine the association between the weight-adjusted waist circumference index (WWI) and the risk of depression in U.S. adults, as well as the potential mediating roles of chronic diseases (hypertension, diabetes, stroke, and coronary heart disease) in this relationship.MethodsData from 7,709 adults aged 20–80 years in the 2017–2023 National Health and Nutrition Examination Survey (NHANES) were analyzed. Logistic regression was used to assess the relationships between WWI (both continuous and categorical) and chronic diseases with depression risk, adjusting for confounders. Subgroup analyses were conducted based on age, sex, race, PIR, education level, marital status, smoking, and drinking status. A restricted cubic spline (RCS) analysis was performed to evaluate the linear relationship between WWI and depression. Mediation analysis was applied to investigate the mediating roles of hypertension, diabetes, and stroke in the WWI-depression relationship.ResultsThe final sample consisted of 7,709 adults with a mean age of 50.8 ± 17.4 years, with a depression prevalence of 17% (1,308 cases). Each unit increase in WWI was associated with higher odds of depression in both crude (OR = 1.031, 95% CI: 1.021–1.040) and adjusted models (OR = 1.029, 95% CI: 1.017–1.041). In quartile analysis, higher WWI levels were linked to an increased depression risk compared to the lowest quartile. Subgroup analyses revealed consistent findings, except for differences observed among males and individuals with a high school education or less. RCS analysis showed a linear relationship between WWI and depression risk. Hypertension (OR = 1.038, 95% CI: 1.018–1.058), diabetes (OR = 1.047, 95% CI: 1.021–1.074), and stroke (OR = 1.102, 95% CI: 1.060–1.146) were independently associated with higher depression odds. Mediation analysis indicated that hypertension, stroke, and diabetes mediated 10.3, 2.4, and 10.0% of the WWI-depression relationship, respectively.ConclusionOur findings suggest that a higher WWI is independently associated with increased depression risk in U.S. adults. Additionally, chronic diseases such as hypertension, diabetes, and stroke are positively correlated with depression risk. Mediation analysis revealed that these chronic conditions partially mediate the relationship between WWI and depression. These results emphasize the utility of WWI as an anthropometric index for predicting depression risk and highlight the importance of maintaining healthy body composition and managing chronic diseases to prevent depression. Interventions targeting both obesity and chronic disease management may prove effective in mitigating depression risk among adults.